Universal transients in polymer and ionic transition metal complex light-emitting electrochemical cells - Reenen, Stephan van; Akatsuka, Takeo; Tordera, Daniel; Kemerink, Martijn; Bolink, Henk J. (Journal of the American Chemical Society, 2013)
Two types of light-emitting electrochemical cells (LECs) are commonly distinguished, the polymer-based LEC (p-LEC) and the ionic transition metal complex-based LEC (iTMC-LEC). Apart from marked differences in the active layer constituents, these LEC types typically show operational time scales that can differ by many orders of magnitude at room temperature. Here, we demonstrate that despite these differences p-LECs and iTMC-LECs show current, light output, and efficacy transients that follow a universal shape. Moreover, we conclude that the turn-on time of both LEC types is dominated by the ion conductivity because the turn-on time exhibits the same activation energy as the ion conductivity in the off-state. These results demonstrate that both types of LECs are really two extremes of one class of electroluminescent devices. They also implicate that no fundamental difference exists between charge transport in small molecular weight or polymeric mixed ionic and electronic conductive materials. Additionally, it follows that the ionic conductivity is responsible for the dynamic properties of devices and systems using them. This likely extends to mixed ionic and electronic conductive materials used in organic solar cells and in a variety of biological systems.